Facilitator and learner's understanding on Roger's core conditions of a person centered counseling (and learning) in the student centered learning environment. - Abu Talib, Mansor (2007)
Student Centered learning (SCL) focuses on the need, abilities, interest and learning styles of the students then of others involve in the educational process. Being students centered engages instructors in a humanistic approach to education in which they function as facilitators of learning (Nuckles, 2000). In counseling and psychotherapy, Person Centered Counseling (PCC) center to the client as a person, not his or her problem. PCC belongs to the humanistic theory of counseling that focuses on the potential of individuals to actively choose and purposely decide about matters related to themselves and their environments. Rogers (1980) emphasized hat people need to be assisted in learning how to cope with situations and to become a fUlly-functioning person. Roger believes that the principles of PCC could be applied outside counseling situation, thus the Person Centered Leaning (PCL) was developed. Relationship between facilitator/counselor and learner is the central criteria hat signified CC and PCL. Evidently, PCC strongly believes hat significant positive changes could not occur except in relationships. In addition, Rogers specified the necessary core conditions in PCC and PCL, I.e. realness, congruence, genuine or transparency in the client/facilitator, acceptance or respect towards the client/learner or unconditional positive regard, and the striving for empathic understanding of the client/learner. These three core conditions are the prerequisite in PCC and PCL for change and effective learning to take place. This paper discusses lived experiences of facilitators and learners in SCL on their understanding of Roger's core conditions. It will give suggestion on methods and others ways to promote PCL as another approach in SCL.